A Review of the Physiological and Immunological Functions of Biliary Epithelial Cells: Targets for Primary Biliary Cirrhosis, Primary Sclerosing Cholangitis and Drug-induced Ductopenias - Chih-Te Wu; Paul A. Davis; VelImir A. Luketic; M. Eric Gershwin (Clinical and Developmental Immunology)
Our understanding of biliary epithelial cells (BEC) in physiobiology and immunology has steadily expanded. BEC transports IgA as well as IgM into bile, synthesizes and secretes various chemokines, cytokines, and expresses adhesion molecules involved in cell interaction and signal transduction. These then suggest a myriad of potential roles for BEC in defense from invading microorganisms as well as the pathogenesis of diverse immunologically driven diseases such as primary biliary cirrhosis (PBC), graft-versus-host disease, and primary sclerosing cholangitis (PSC). Despite the progress, there still remain many areas of BEC biology that require further investigation. Most importantly, it remains to be clarified that the extent to which the immunologic activities observed in BEC represent a BEC response to tissue injury or whether BEC themselves are the active participants in the pathogenesis of various cholestatic immunological diseases, including PBC and PSC.